Colchicine may assist in reducing granulation tissue in junctional epidermolysis bullosa - Minhee Kim, MBBS; Swaranjali Jain, BMedSci (Hons); Adam G. Harris, MBChB; Dedee F. Murrell, MA, BMBCh, FAAD, MD, FACD, FRCP (Edin) (Wolters Kluwer, 2016)
Epidermolysis bullosa (EB) is a rare, inherited blistering genodermatosis. Patients with junctional EB (JEB) due to LAMB3 mutations have widespread blisters and erosions of skin, mucosae, and nails, creating significant physical, emotional, and psychosocial burdens. Here we report the use of colchicine for ameliorating hypergranulating wounds in a 41-year-old female with JEB generalized intermediate. Her skin wounds and granulation tissue gradually exacerbated under silicone dressings such that she became profoundly anemic. Subsequently, she was commenced on colchicine 500 μg daily on the basis that it may inhibit cell proliferation and be anti-inflammatory. After a 6-month trial of colchicine, she had an objective and subjective improvement in her validated EB Disease Activity and Scarring Index activity and damage scores and Quality Of Life in EB score with less skin erosions, granulation tissue, and erythema. In addition, her anemia resolved. She denied any gastrointestinal side effects. The exact mechanism of colchicine in assisting reduction of the blistering, erosions, and granulation in JEB is unclear, but the anti-inflammatory and antimitotic properties of colchicine may be partially responsible for this process. Keywords: anti-inflammatory, colchicine, granulation tissue, junctional epidermolysis bullosa